Talent Management and the Communication of Talent Status - Sumelius, Jennie; Smale, Adam (Routledge, 2021)
This chapter reviews selected literature on talent status communication from the individual employee perspective, which is a small but rapidly emerging area within Talent Management (TM) research. Corporate TM tends to be either inclusive, in that all employees are considered talent, or exclusive, in which only a certain small group of employees are viewed as talent. The main communication challenges of open TM systems relate to the consistent clarification of the “rules of the race” on the one hand, and the effective management of key tensions on the other. In terms of the “rules”, transparency requires the organization to send strong and consistent signals about the meaning of talent so that employees are able to develop shared interpretations. A related tension is how to manage communication about what talent pool members can expect in terms of exclusive treatment such as “talent only” training and development opportunities.
Keywords: fi=Henkilöstöjohtaminen|en=Human Resource Management|